(untitled) (Proceedings of International Conference on Special Education, 2023)
In Malaysia, studies on students with special needs in technical and vocational education are lacking. Therefore, this study aims to identify the level of readiness of trainee teachers towards the implementation of the teaching and learning process for technical and vocational subjects namely Design and Technology. This study uses a survey method using a 4-point Likert scale questionnaire as a research instrument involving a sample of 154 teacher trainees at the Technical Education Campus Teacher Education Institution who took the Design and Technology (RBT) course. The size of the selected respondents was by simple random sampling using Krejcie & Morgan’s Sample Size Determination Table. Descriptive analysis was used to obtain the mean value, standard deviation, frequency, and percentage to see the level of preparedness of trainee teachers towards Special Needs Students (SNS) in TVET subjects. The findings of the study show the level of knowledge and skills of trainee teachers regarding the implementation of teaching and learning of Design and Technology subjects for students with Special Needs (SNS) which is overall at a moderate level. The results of the analysis found that the level of knowledge and skills of trainee teachers at Teacher Education Institutions concerning the implementation of the teaching and learning of Design and Technology subjects for Students with Special Needs (SNS) needs to be improved. This study is expected to provide input on the level of preparedness of trainee teachers at the Technical Education Campus Teacher Education Institution in teaching students with special educational needs in TVET subjects. Improving the knowledge and skills of Design and Technology trainee teachers at the Technical Education Campus Teacher Education Institution will have a positive impact on the effectiveness of the teaching and learning delivered by the trainee teachers, which in turn can improve the quality of learning for Special Needs Students (SNS) in the classroom. In conclusion, every trainee teacher needs to be given sufficient training and education to help Special Needs Students (SNS) in Design and Technology subjects.